ANALISIS PENGEMBANGAN OBJEK DANAU WISATA BANDAR KAYANGAN LEMBAH SARI KECAMATAN RUMBAI DI KOTA PEKANBARU - Yasni "; Sujianto "; Ari Kresnaputra Agus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
ABSTRACT This research is aimed to find out visitors response about the analysis of the development of tourism object Danau Bandar Kayangan Lembah Sari Kecamatan Rumbai Pekanbaru, especially in the development of its facility. Writer used Spiliane theory (1994 : 25), which is said that facility is a supporting tool of the tourism object daily operational, to accommodate visitors need, indirectly support growth but develop at the same time or after the attraction. Writer used ordinal scale for measuring, which is likert scale, it is designed to ease respondent to answer some levels in objects which are going to measured (Mirwan, 2010 : 36). Writer identified three main problem: visitors respondent about the development of the facility according to public facility, supporting and complementing tool in Danau Bandar Kayangan Lembah Sari Kecamatan Rumbai, Pekanbaru. Writer found that visitors think that facilities are good enough, eventhough they need to be fixed in some aspects by improving and developing promotion and marketing, and also fix the facilities in the location. Obstacles found this fixation are: lack of fund, lack of management ability, and lack of awareness among visitors. Writer suggest to culture and tourism department to care more about the waterfacility. Writer also suggest to the management party to create some rules for managingtrash in the location. Specialis care for mushollah, and toilet. Key words: facilities, tourism, development, tourism object.